Advanced Digital Modeling of Stress–Strain Behavior in Rock Masses to Ensure Stability of Underground Mine Workings - Demin, Vladimir; Kalinin, Alexey; Tomilova, Nadezhda; Tomilov, Aleksandr; Akpanbayeva, Assem; Shokarev, Denis; Popov, Anton (Salehan Institute of Higher Education, 2025)
This study focuses on optimizing underground support systems through advanced numerical modeling and geomechanical assessment. The research aims to refine reinforcement parameters for underground mine workings by analyzing the stress-strain behavior of rock masses using Rocscience RS2 software. The study integrates geological and geotechnical data, including field observations and numerical simulations, to enhance the accuracy of support system designs. The methodology is based on the finite element method (FEM) and the Hoek–Brown softening model, allowing the identification of plastic deformation zones and stress redistribution patterns. The results confirm that maximum stress increases by 35–40% for every 100 m of depth, necessitating enhanced reinforcement. The study evaluates hybrid support systems, specifically steel-polymer bolts with shotcrete, demonstrating a 15% reduction in plastic deformations compared to conventional methods. The findings highlight the importance of continuous geotechnical monitoring and adaptive reinforcement strategies to ensure stability in highly fractured rock masses. The proposed approach provides a more precise prediction of excavation stability, contributing to the development of safer and more efficient underground mining practices. Future research may include the integration of intelligent monitoring systems equipped with real-time sensors to further optimize support strategies and long-term stability assessments. Doi: 10.28991/CEJ-2025-011-03-014 Full Text: PDF